1994
DOI: 10.1136/gut.35.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between clinical activity, endoscopic severity, and biological parameters in colonic or ileocolonic Crohn's disease. A prospective multicentre study of 121 cases. The Groupe d'Etudes Therapeutiques des Affections Inflammatoires Digestives.

Abstract: The relationships between clinical activity, endoscopic severity, and biological parameters in Crohn's disease have not been thoroughly investigated and a link was therefore sought between these three elements. The following parameters were determined simultaneously in 121 consecutive patients with colonic or ileocolonic Crohn's disease: Crohn's disease activity index, Crohn's disease endoscopic index of severity, and serum albumin, CE2-globulin, a,-antitrypsin, orosomucoid, C reactive protein, erythrocyte sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
188
2
8

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(205 citation statements)
references
References 19 publications
5
188
2
8
Order By: Relevance
“…CRP levels are found to be weakly associated with clinical activity indices by several authors [14,[19][20][21] , although this has not been reported consistently [22] . Colombel et al reported a striking correlation of CRP levels with radiologic fi ndings of perienteric inflammation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…CRP levels are found to be weakly associated with clinical activity indices by several authors [14,[19][20][21] , although this has not been reported consistently [22] . Colombel et al reported a striking correlation of CRP levels with radiologic fi ndings of perienteric inflammation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The GETAID group has repeatedly shown that endoscopic activity of Crohn's disease correlates either poorly or not at all with a clinical disease activity index 6,7,29 . Similarly in ulcerative colitis, macroscopic changes at colonoscopy have correlated poorly with the PT clinical index, so an objective measure of inflammation is not necessarily reflective of a patient's symptoms 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Imaging modalities have also been used to assess disease activity. This approach avoids the subjective element of symptom inquiry, but it correlates poorly with active symptoms and it is problematic to repeat imaging, endoscopic or radiological methods for sequential assessment of activity 6,7 .…”
Section: Formentioning
confidence: 99%
“…Systemic markers of inflammation, such as ESR, CRP, platelet count and white blood cell count are commonly used in clinical practice, but correlation to ongoing intestinal inflammation is poor [35] . Therefore, we monitored the consecutive changes in ESR (Figure 4) and complete blood count (CBC) of our patients.…”
Section: Discussionmentioning
confidence: 99%